Improving the performance of an active greenhouse dryer by integrating a solar absorber north wall coated with graphene nanoplatelet-embedded black paint - Selimefendigil, Fatih; Sirin, Ceylin; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2022)
Greenhouse drying systems are sustainable and clean applications for preserving agricultural crops. In this work, a single-slope greenhouse drying system has been modified with solar absorber and thermally insulated north wall. Also, the designed and manufactured north wall has been coated with graphene nanoplatelet-embedded black paint. Greenhouse dryers with north wall and nano-embedded north wall modifications have been experimentally compared with a conventional greenhouse dryer. Main goal of this research is to upgrade the performance of a greenhouse drying system without using any auxiliary heating device and complex structural components. According to the experimental outcomes, drying time was reduced as 75 and 90 min by utilizing north wall and nano-enhanced north wall, respectively. Furthermore, exergy efficiencies of greenhouse dryers with north wall and nano-enhanced north wall were attained as 4.67% and 5.38%, respectively while this value for conventional greenhouse dryer obtained between 2.61 and 2.70%. Moreover, utilizing graphene nano platelets in black paint improved the specific moisture extraction rate as 40% in comparison to conventional greenhouse dryer.
Keywords: Greenhouse dryer; Solar drying; North wall; Graphene nanoplatelets; Black paint